2019
DOI: 10.1111/phn.12630
|View full text |Cite
|
Sign up to set email alerts
|

“Social justice is a dream”: Tensions and contradictions in nursing education

Abstract: Objective The purpose of this study was to explore nurse educators’ conceptualizations of social justice in theory courses. The findings contextualize the role of nurse educators in promoting social justice among future health care providers and the relevance of their perspectives on social justice. Design This descriptive qualitative study was completed utilizing constructivist grounded theory methods. Sample and Measurements I interviewed 28 nurse educators teaching theory courses in Baccalaureate nursing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 41 publications
(39 reference statements)
0
32
0
Order By: Relevance
“…Conceptualizing social justice as awareness does not necessarily constitute social justice teaching but can be viewed as a step in that direction, similar to critical consciousness. Faculty pedagogical approaches and conceptualizations can be situated within various contexts, including upbringing and formative experiences, educational paths, and layers of prevailing institutional priorities and structures (Valderama‐Wallace & Apesoa‐Varano, 2019a, 2019b). This model conveys the system that upholds whiteness and the blueprint for change.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conceptualizing social justice as awareness does not necessarily constitute social justice teaching but can be viewed as a step in that direction, similar to critical consciousness. Faculty pedagogical approaches and conceptualizations can be situated within various contexts, including upbringing and formative experiences, educational paths, and layers of prevailing institutional priorities and structures (Valderama‐Wallace & Apesoa‐Varano, 2019a, 2019b). This model conveys the system that upholds whiteness and the blueprint for change.…”
Section: Resultsmentioning
confidence: 99%
“…How might we understand the relationship between nursing education and society? Nursing institutions state that social justice is a core professional value, despite inconsistent conceptualizations across American Nurses Association documents (Valderama‐Wallace, 2017) and among nurse educators (Valderama‐Wallace & Apesoa‐Varano, 2019a). The prevailing emphasis on individualism and egalitarianism embodies whiteness and colonialism, decontextualizing health and preventing examination of root causes of health inequities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have been made on race and ethnic background among nurse educators [77,78], but we were unable to find research on nurse educators' prior education with respect to sustainability studies, environmental determinants of health, personal experience of living in communities exposed to environmental hazards or prior experience working with environmental justice. We were also unable to find Swedish studies or national evaluations concerning race and ethnic background of nurse educators, their competence with respect to environmental and sustainability issues, if these aspects are considered in recruitment, or the role nurse educator background (see Valderama-Wallace and Apesoa-Varano [64,66,67]) plays in teaching global health.…”
Section: Obstacles To Including Gh Ej and Sdh In Nursing Curriculamentioning
confidence: 99%
“…Our concern is that being able to take actions should follow an interpretation based on something other than personal values and backgrounds (cf. Valderama-Wallace and Apesoa-Varano, [66,67]), also with the risk that GH content becomes 'fluid' and related to partial issues, while not being related to any social context, understanding and explanations. In our data, we found that GH, as expressed in the course syllabi, are not understood, discussed or interpreted underpinned by any explicit theoretical approach.…”
Section: Lack Of Theoretical Perspectivementioning
confidence: 99%